2012
DOI: 10.1021/es203019y
|View full text |Cite
|
Sign up to set email alerts
|

Relative Decay of Fecal Indicator Bacteria and Human-Associated Markers: A Microcosm Study Simulating Wastewater Input into Seawater and Freshwater

Abstract: Fecal contaminations of inland and coastal waters induce risks to human health and economic losses. To improve water management, specific markers have been developed to differentiate between sources of contamination. This study investigates the relative decay of fecal indicator bacteria (FIB, Escherichia coli and enterococci) and six human-associated markers (two bacterial markers: Bacteroidales HF183 (HF183) and Bifidobacterium adolescentis (BifAd); one viral marker: genogroup II F-specific RNA bacteriophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 35 publications
4
57
2
Order By: Relevance
“…In contrast, slower decay rates of Bacteroidales markers exposed to sunlight have been observed by others [105,108,110]. Studies also reported that the decay rates of the several Bacteroides markers including human-specific Bacteroides (BsteriF1, BuniF2, GenBac3, HF183, HF134, and HumM2) in freshwater were somewhat greater than the corresponding decay rate in seawater [106,112]. Bae and Wuertz [108] used propidium monoazide (PMA)-qPCR to differentiate between live and dead cells or extracellular DNA.…”
Section: Decay Of Human-specific Bacteroides Markers In Environmentalmentioning
confidence: 98%
“…In contrast, slower decay rates of Bacteroidales markers exposed to sunlight have been observed by others [105,108,110]. Studies also reported that the decay rates of the several Bacteroides markers including human-specific Bacteroides (BsteriF1, BuniF2, GenBac3, HF183, HF134, and HumM2) in freshwater were somewhat greater than the corresponding decay rate in seawater [106,112]. Bae and Wuertz [108] used propidium monoazide (PMA)-qPCR to differentiate between live and dead cells or extracellular DNA.…”
Section: Decay Of Human-specific Bacteroides Markers In Environmentalmentioning
confidence: 98%
“…Ideally, MST markers and FIB will have similar fates and transport behaviors governed by their concentrations in polluting matrices, extraintestinal survival, growth rates after excretion, and mobility in the environment (10,11). Of these factors, survival of FIB and MST markers plays an integral role in determining their fate and transport in the environment, since survival can strongly influence prevalence in both fecal sources and water environments.…”
mentioning
confidence: 99%
“…However, the validity of the tiered approach depends upon a close correlation between the quantities of the Bacteroidales gene markers and the standard FIB of the target animal species after feces is excreted into the water so that the gene marker detection assay could reliably indicate to the animal species that caused the increase in the monitored level of the standard FIB. As such, the understanding of the relative decay rates of the Bacteroidales gene markers and the standard FIB in water have important implications to their utility in the tiered approach (Dick et al 2010;Jeanneau et al 2012;Tambalo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently not known how the combined effects of the concentration of DO and the intensity of light affect the dynamics of the DNA and RNA of the Bacteroidales gene markers relative to that of the standard FIB, and which type of the markers (DNA vs RNA) would be more suitable to complement the standard FIB in the tiered approach under different DO and light conditions. Thus far, studies on the decay of the Bacteroidales gene markers have been mainly for those associated with human feces (e.g., Savichtcheva et al 2005;Dick et al 2010;Jeanneau et al 2012;Ahmed et al 2014). There are far fewer reports on the decay of the gene markers of other animal sources such as cattle (e.g., Okabe and Shimazu 2007;Tambalo et al 2012).…”
Section: Introductionmentioning
confidence: 99%